PPLICATION OF A FUNCTIONAL CORRELATION ENERGY IN COMPARISON WITH SCF CALCULATIONS G2 THEORY FOR DISSOCIATION ENERGIES IN MOLECULES LA SERIE CH4-nCln - Cjuno H., Jesús A. (2004)
The objective of this work has been to study the behavior of the one correlation energy functional Ec=[ño(R),ñ2o(R),{z}], through the calculation the dissociation energy in molecules of the series methane - tetrachloromethane (Ch4-nCln) obtained from the group of G2 molecules. The functional, once incorporate to the program Gaussian 92/DFT has been used to develop comparative monoconfigurational calculations with the method G2 implemented in the versions Gaussian 98 and 03. The results show a growing error with relationship to the increment of chlorine atoms, or the same thing with the number of electrons (N). In this sense, the functional show that the dependence with N can be improved.